Online SoC Balancing Strategy for Distributed Single-Stage MMC-Based BESS - Garay, Juan A. P.; Almeida, Pedro M.; Barbosa, Pedro G. (Eletrônica de Potência, 2026)
This paper proposes an online state-of-charge (SoC) balancing strategy for a distributed single-stage Modular Multilevel Converter-based Battery Energy Storage System (MMC-BESS). The main contribution is the development of a low-complexity sorting-based selection algorithm integrated into the smart-battery concept, enabling real-time energy redistribution among submodules without requiring additional auxiliary balancing circuits. The proposed method operates jointly with a phase-disposition pulse width modulation (PD-PWM) strategy and is coordinated with conventional grid current control in the synchronous reference frame and circulating current suppression control, thereby ensuring stable converter operation. The complete three-phase MMC-BESS, composed of 18 submodules per arm, was modeled and validated using PSCAD/EMTDC simulations. The performance of the proposed balancing algorithm was evaluated under multiple operating conditions, including active power injection, active power absorption, and reactive power support. Simulation results demonstrate effective SoC equalization across all submodules while maintaining high-quality AC voltage and current waveforms and while ensuring suppression of internal circulating currents. The simulation results confirm the robustness, scalability, and practical applicability of the proposed control strategy, highlighting its potential for improving reliability, extending battery lifetime, and enabling MMC-based BESS to provide ancillary services and support large-scale integration of renewable energy sources.